Percutaneous Electrocauterization (Electrosclerotherapy) to Treat Cutaneous Hemangioma- our experience in Apollo Hospitals Dhaka (Pulse, 2014)
Introduction Percutaneous Electrosclerotherapy technique for the treatment of cutaneous hemangioma is introduced as an alternative and minimally invasive treatment mode. The aim of the study was to evaluate the response of percutaneous electrosclerotherapy on cutaneous hemangioma, as monotherapy or in adjunct to surgery. Materials and Methods Fourteen patients with 10 females and 04 males underwent percutaneous electrosclerotherapy for the treatment of cutaneous hemangioma mostly on head and neck in Plastic and Cosmetic Surgery department of Apollo Hospitals Dhaka from January 2009 to June 2010. Percutaneous Electrosclerotherapy was applied through a Colorado needle with an intention to cauterize the bulk of the lesion at the tip of the needle but not burning the skin. Pre and post operatively the size of the lesions were measured to see the percentage of regression. Results Percutaneous Electrosclerotherapy was done in all 14 cases. Most of the lesions (78%) were smaller in size (